IMPLEMENTASI PENGELOLAAN ALOKASI DANA DESA (ADD) DALAM PEMBERDAYAAN MASYARAKAT DESA RIJANG PANUA - Afrianti, Yuyun; Jabbar, Abdul; Yasin, Akhmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to examine the implementation of Village Fund Allocation (ADD) management in an effort to improve the capacity and independence of the Rijang Panua village community, with a focus on communication, resources, implementers’ attitudes, as well as bureaucratic organizational structure and transparency. The study uses a descriptive quantitative approach with a sample of 88 respondents, determined using the simple random sampling method. Data were collected through questionnaires, interviews, observations, and documentation, then analyzed using validity and reliability tests, as well as simple regression analysis with SPSS. The findings reveal that the implementation of ADD management falls into the very good category, with an average achievement of 89%, while community empowerment is in the good category, averaging 87%, covering access, participation, control, benefits, and independence. However, the simple regression results indicate that Village Fund Allocation (ADD) management only contributes 0.9% to supporting the improvement of community capacity, while 99.1% is influenced by other variables. This indicates that although ADD implementation runs well, its impact on community independence remains limited.